Grands ensembles, cités ouvrières, logement social : patrimoines habités, patrimoines contestés - Elizabeth Auclair; Anne Hertzog (EchoGéo)
Metropolitan growth, de-industrialization, urban sprawl, renovation, gentrification, impoverishment and tourism development are among the many urban and social changes that affect suburbs and peripheries of French towns and cities. These processes interact with the attribution of heritage status to some areas. The present number of this journal contains five articles that explore aspects of the recognition of urban heritage. Attention is focused on heritage features in areas undergoing recomposition, and on 'actors' involved, especially the position of residents in these processes.